ANALISIS PENERAPAN PEMBELAJARAN GURU SETELAH SATU TAHUN MASA COVID-19 - Siregar, Sri Utami Kholilla Mora; Siregar, Nurhasanah; Kasmawati, Kasmawati (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2022)
The purpose of this study was to analyze distance learning applied by teachers after one year of experiencing a non-natural Covid-19 disaster. This research was conducted qualitatively, with data analysis techniques through an abstraction process based on the data obtained by taking into account the substantive object of research. Data collection through questionnaires and interviews. The subjects of the research were science-physics teachers with 16 respondents who teach at schools in Central Tapanuli, South Tapanuli and Madina. The results showed that the learning media had not optimally utilized online learning media through virtual face-to-face, the dominant teacher used the WhatsApp group media, and google classroom, the media supporting the delivery of teacher material mostly provided learning videos from youtube, the teacher's appeal for students to learn through learning events on TVRI by 18.8%. In the experimental learning stage, the teacher directs students to experiment through 37.5% student handbooks, 25% worksheets, 18.8% videos, while group assignments are other procedures revealed by one respondent. Classical student learning outcomes achieved >80% as many as 2 respondents, 40%-50% as many as 3 respondents, and 10% there was one respondent, the rest between 75% to 65%.